Peningkatan halaju suapan maksimum penginterpolasi CNC dedenyut rujukan menggunakan pengaturcaraan selari - Ahmad Fakhri, Ab. Nasir (2011)
Maximum allowable feed rate for reference-pulse Computer Numerical-Control (CNC) system is limited by the interpolator iteration speed. In other word, it means higher iteration speed corresponds to higher maximum allowable feed rate. To develop interpolator with higher maximum allowable feed rate, the proposed interpolator is aimed to execute the interpolator tasks in concurrent manner. In the recent years, the computer industry has changed a lot in term of hardware development. Multi-core processors were introduced whereby a single computer has two processors working on it and contain multiple logical processors in a single package. By using multi-cores environment, algorithm has to be changed in order to fully utilise the speed of the processors. This situation is also required in interpolator algorithm. The existing interpolator is not using parallel programming which every task have not been execute simultaneous in concurrent manner although using multi-cores processor computer, thus, the more time is needed for the iteration time especially for a complex and large scale of process. The main research objective is to modify the existing Wan Yusoff reference-pulse CNC interpolator and Omirou reference-pulse CNC interpolator using parallel programming to increase maximum allowable feed rate. The proposed interpolator is developed using parallel programming in C/C++ language through Open Multi-Processing (OpenMP). The proposed interpolator was compared with Wan Yusoff (2003) interpolator and Omirou and Nearchau (2006) interpolator through computer simulation and experiment with servomotor. Computer simulations which were conducted on various parametric curves indicated that the proposed interpolator are at least 37.04% more efficient compared to Wan Yusoff (2003) interpolator and at least 20.10% more efficient compared to Omirou and Nearchau (2006) interpolator. Finally, the experimental results verify that the maximum allowable feed rate for the proposed interpolator are higher than Wan Yusoff (2003) interpolator and higher than Omirou and Nearchau (2006) interpolator. The proposed interpolator is ready for new era of multi-processors.